Doen metodologies wat akademies verkondig word: Ontwikkelings en geleenthede vir homiletiek in SA - Wepener, Cas J.; Nell, Ian A. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2023)
Bringing methodology and theory closerDevelopment and challenges in South African homiletics. The homiletic landscape in South Africa is rich and varied. In this contribution, we attempt to paint with broad brushstrokes this landscape. We write as practical theologians with a shared love for homiletics, but also with an interest in doing what we preach in terms of research and teaching. Put differently, we argue in the light of existing literature that there should be congruence between theories we advance, and methodologies we employ. We dwell on themes such as decolonisation, justice and reconciliation, poverty and inequality that are characteristic of our homiletical landscape. We conclude with the thought that as Christianity in South Africa grows and preachers increase in number, so do the opportunities for empirical academic involvement in preaching. However, the occasion also poses a challenge for academics engaged in homiletics, namely, to practise what they preach by bringing theory and method in a closer relationship.ContributionThe article engages current homiletical research in South Africa by means of a literature study, specifically highlighting the challenges and opportunities posed to the discipline of Homiletics within a postcolonial South African context, and at ecumenical faculties of Theology. These challenges and opportunities are especially important for a discipline such as Homiletics in South Africa with its strong Protestant and Reformed roots, to reflect on future methodologies pertaining to research and teaching.